A measurement of the CP asymmetry difference between [Lambda]+c→pK−K+ and pπ−π+ decays - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Berninghoff, Daniel; Braun, Svende; Comerma-Montells, Albert; De Cian, Michel; Dziewiecki, Michal; Esen, Sevda; Gerick, David; Grabowski, Jascha; Grünberg, Oliver; et al. (Journal of high energy physics, 2018)
The difference between the CP asymmetries in the decays Λ c + → pK−K+ and Λ c + → pπ−π+ is presented. Proton-proton collision data taken at centre-of-mass energies of 7 and 8 TeV collected by the LHCb detector in 2011 and 2012 are used, corresponding to an integrated luminosity of 3 fb−1. The Λ c + candidates are reconstructed as part of the Λ b 0 → Λ c + μ−X decay chain. In order to maximize the cancellation of production and detection asymmetries in the difference, the final-state kinematic distributions of the two samples are aligned by applying phase-space-dependent weights to the Λ c + → pπ−π+ sample. This alters the definition of the integrated CP asymmetry to A CP wgt (pπ−π+). Both samples are corrected for reconstruction and selection efficiencies across the five-dimensional Λ c + decay phase space. The difference in CP asymmetries is found to be ΔAwgtCP=ACP(pK−K+)−AwgtCP(pπ−π+)=(0.30±0.91±0.61) %,ΔACPwgt=ACP(pK−K+)−ACPwgt(pπ−π+)=(0.30±0.91±0.61) %, \begin{array}{c}\hfill \Delta {A}_{CP}^{\mathrm{wgt}}={A}_{CP}\left(p{K}^{-}{K}^{+}\right) - {A}_{CP}^{\mathrm{wgt}}\left(p{\pi}^{-}{\pi}^{+}\right)\hfill \\ {}\hfill = \left(0.30 \pm 0.91 \pm 0.61\right)\ \%,\hfill \end{array} where the first uncertainty is statistical and the second is systematic. Open image in new window
Im Titel wird "Lambda" als griechischer Buchstaben dargestellt
Im Titel sind "+" und "c" untereinander geschrieben: "+" hochgestellt, "c" tiefgestellt
Im Titel werden "+" und "-" hochgestellt
The LHCb collaboration: R. Aaij, P. d'Argent, S. Bachmann, D. Berninghoff, S. Braun, A. Comerma-Montells, M. De Cian, M. Dziewiecki, S. Esen, D. Gerick, J.P. Grabowski, X. Han, S. Hansmann-Menzemer, M. Kecke, B. Khanji, M. Kolpin, R. Kopecna, B. Leverington, J. Marks, D.S. Mitzel, T. Nikodem. S. Neubert, M. Neuner, A. Piucci, M. Stahl, S. Stemmle, J. van Tilburg, U. Uwer, A. Zhelezov [und weitere]
Gesehen am 30.04.2019